教師學與新師資培育政策─一個「責任良師」造就「責任公民」的新世代 Teacher-ship and the New Policy of Teacher Education -- A New Era of Responsible Citizenship to be Educated by Responsible Qualified Teachers - 鄭崇趁 Chung-Chen Cheng (National Changhua University of Education, 2015)
教師是國家教育事業的靈魂，教師的素質決定教育的成敗，教師的表現決定學校教育的興旺或低迷。教師是需要學習的，學習成為「責任良師」的系統知識稱為「教師學」。「教師學─鐸聲五曲」的主要內容：首部曲「鐘鳴大地．人師」，敘述教師的生命願景與教育志業。二部曲「朝陽東昇．使命」，描述教師的核心價值與專業示範。三部曲「春風化雨．動能」，闡明教師的核心能力與智慧資本。四部曲「明月長空．品質」，探討教師的教育品質與績效責任。五部曲「繁星爭輝．風格」，分析教師的系統思考與順性揚才。「教師學」結合教師培育體制相關研究，對「新師資培育政策」有前瞻規劃建議：（1）將「教育實習」移至「教師資格檢定考試」之後，並以「教學碩士學分」培育，規範教育實習須兼取領域（學科）教學證照。（2）試辦教師資格檢定考試，轉為「國家高考」，將中小學教師身分界定為國家專門職業公務員。（3）全面提高中小學師資碩士化比例至85%以上，提高專長任教比例（有教學證照）80%以上。（4）將「教師學」列為教師職前教育及專業進修課程，將「教育經營學」及「校長學」列為校長、主任培育課程。（5）闡揚「新五倫及其核心價值」教育。期待「教師學」及「新師資培育政策」，可以開創一個「責任良師」造就「責任公民」的新世代。 Teachers are the soul of educational enterprise at all levels. Teacher quality plays important roles in determining the success or failure of education, and also, teacher performance determines whether school education will prosper or dwindle. In order to be a responsible qualified teacher, teachers need to learn a systematic body of knowledge. Teacher learning is an aspect especially emphasized in a book on Teacher-ship which is consisted of the following five essentials. The first part, being a teacher, tries to describe teachers' professional life and educational aspirations. Then the second, carrying a mission, aims to focus on teachers' core value and professional demonstrations. The third, being dynamic, to elaborate teachers' core competencies and knowledge capitals. The fourth, maintaining quality, it discusses teachers' educational quality and accountability. Finally the fifth, varying styles, it analyses teachers' systematic thinking and adaptive knowledge management skills. Relevant studies of teacher training are incorporated in the book on Teacher-ship, offering the following suggestions to the new teacher training policy: (1) To move the internship to a time after the qualification examines, then to consider making internship as part of teaching master degree credits. In addition, practicing teachers should acquire their teaching certificates in selected subject matter areas while teaching at schools. (2) To consider making teachers' qualification examines as national examines for higher officials, treating teachers as professionals serving in official positions. (3) To raise the percentage of junior high and elementary school teachers having educational degree at master degree level to above 85%. Also, to raise the proportion of qualified teachers in subject matter areas up to 80%. (4) Making Teacher-ship a course in teacher education and professional development programs. Further, courses on Educational management and Principal-ship should be considered as essential courses for programs aiming at preparing principals and directors. (5) To elaborate the new five ethics and their core values. It is expected that the Teacher-ship and the new teacher education policy advocated in this study would open a new era of responsible qualified teachers and responsible citizenship.